Korupcja jako problem teoretyczny i społeczno-ekonomiczny - Nowakowski, Krzysztof (Wydział Prawa i Administracji UAM, 1996)
Corruption is a universal, multifaceted and multifarious phenomenon that has numerous factors to its name. Effects of corruption, even if at a similar level in particular countries, differ as well. The causes, however, are always the same: the existence of rare goods - including quasi-public ones - distributed outside the market, and people responsible for the distribution. Corruption can be analyzed as an economic phenomenon (within the context of the economic theory of human behaviour, theory of games, institutionalism, theory of property rights and transaction costs) of the supply-demand-, costs- and property relations. As a sociological phenomenon it provides a context for exchange processes (naturalization, familiarization of social relations within a noninstitutionalized system of interest expression and vis-a-vis social anomy). As a psychologic-cultural phenomenon, corruption creates a specific atmosphere of establishing contacts, it confers peculiar features and defines the effects of such phenomena in the system. With the additional element of the gift institution, corruption within Polish medical care is yet another issue. In Poland corruption can be analyzed in subject-relational and object aspects (eg penetration of goods such as concessions, information, custom duties, reductions, certificates, norms). The said analyses allow to formulate the chief thesis of the paper, namely, that corruption has a positive impact (eg as an element of competitiveness, pluralization, acceleration of deal making, limiting the distance). However, the negative impact prevails: in this paper defined as a loss of economical and social alternative inherent in economic growth, pathology of institutions, then human attitudes towards the economy and the state which are pertinent to the development of the market and the civic society. Yet, this is a process - though long - one can fight, even if it involves a number of tools, starting with those of legal and economic nature.
Corruption as a theoretical and socio-economic issue